Impact of Inoculation with Bacterial Bio-Fertilizers and Foliar Spraying with Yeast Suspension on Some Vegetative and Productive Indicators of Protected Tomato (Solanum lycopersicum L.) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
The research was conducted in an unheated plastic house in Al-Haffah area (Lattakia Governorate) during the spring season of the 2025 agricultural year. The research aimed to study the effect of soil fertilization with different types and genera of bacteria and foliar spraying with yeast extract on some vegetative growth indicators and production indicators of the tomato hybrid "Mandaloun F1". The study included five treatments: control (untreated plants), foliar spraying with yeast suspension, soil fertilization with the first bacterial inoculant M1 (Azotobacter chroococcum, Frateuria aurantia, Bacillus megaterium), the second M2 (Azotobacter chroococcum, Pseudomonas fluorescens, Bacillus circulans), and the third M3 (a mixture of the two previous bio-fertilizers, M1 and M2).The research was implemented using a Complete Randomized Block Design with three replications per treatment. The results showed the positive effect of both inoculation with bacterial fertilizers and spraying with yeast extract on the studied traits. The treatment with the third bio-fertilizer inoculant (the mixture of M1 and M2) significantly outperformed the other treatments and achieved the best results, recording the highest values compared to the control in: number of leaves per plant (33.7 vs. 30.3 for control), leaf area (17394 cm² vs. 11617 cm² per plant for control), leaf area index (5.10 vs. 3.41 for control), total number of flowers (55.2 vs. 40.7 flowers/plant for control), number of fruits (45.7 vs. 30.1 fruits/plant for control), average fruit weight (121.7 g vs. 113.1 g for control), yield per plant (5.56 kg vs. 3.40 kg for control), and yield per unit area (16.3 kg/m² vs. 9.9 kg/m² for control).
Keywords: tomatoes (Solanum lycopersicum.L), bacterial biofertilizers (PGPR), yeast extract, Vegetative and productivity indicators.